KEGIATAN TAMAN BACAAN MASYARAKAT (TBM) SUMBER ILMU RUANG PUBLIK BINAAN SKB DI KOTA PAYAKUMBUH - Mona Sari (Universitas Negeri Padang, 2014)
This research is conductem by the high participation of the community to visit the TBM Sumber Ilmu. TBM Sumber Ilmu activities under control of Payakumbuh SKB, consists of selection of location, socialization, availability of facilities and infrastructure, placement time, implementation of management and condition of the book collections. This research is designed as descriptive quantitative research. The research subjects are the visitors of TBM Sumber Ilmu. The results of this research are expressed most of the visitors stated that all the aspect-selection of the location, socialization, availability of facilities and infrastructure, placement time, implementation of management and the condition of the books collection are very good.